Investigation on Some Biochemical and Clinical Parameters for Pregnancy Toxemia in Akkaraman Ewes - Balikci, Engin; Yildiz, Atilla; Gurdogan, Fuat (Medwell Online, 2009)
The aim of this study was to investigate some clinical and biochemical parameters for subclinical and clinical pregnancy toxemia and to determine the effect of early diagnosis on the success of curing. According to the results of clinical and biochemical parameters, 16 ewes were healthy (control group), 11 ewes had subclinical pregnancy toxemia (subclinic group) and 15 ewes had clinical pregnancy toxemia (clinic group). There was an increase at the levels of glucose, albumin, globulin in clinic group and Ca both in clinic and subelinic groups and a decrease at the levels of urea, AST, ALT in clinic group and BHBA both in clinic and subclinic groups after the treatment when compared with the period before treatment. Cure rates for subclinic and clinic groups were determined as 100% (11/11 ewes) and 73% (11/15 ewes), respectively. The parameters such as BHBA, glucose, ALT and AST should be taken in care especially in the period of last 6 weeks of pregnancy in ewes for early diagnosis of subclinical pregnancy toxemia.
Keywords: Pregnancy toxemia; beta-hydroxybutyrate; glucose; ewe; biochemical; parameters; diagnosis